A compreensão do conteúdo jornalístico digital de São Borja por deficientes visuais - (:unkn) unknown (Universidade Federal do Pampa, 2023)
This research aims to understand how access to digital news journalistic sites, Portal Fronteira and Rádio Cultura AM 1260, occurs by disabled people of the Association of the Visually Impaired of São Borja (ADEVASB). In order to identify the access to these media, we sought to Work with reception analytics to understand the experiences and challenges faced by visually impaired people in accessing local digital media. The research highlights the Laws that, among them, highlight the provision that ensures the rights of citizens with disabilities in Brazil, their inclusion in society, as well as accessibility in physical and digital environments. Data collection was carried out through semi-structured interviews with visually impaired citizens. However, from the analysis and the interviews conducted, it can be concluded that in the digital journalistic sites Portal Fronteira and Rádio Cultura AM 1260, There are no accessibility resources, support, or tools available that can contribute to access to information for people with visual impairments.
Keywords: Jornalismo eletrônico; Pessoas com deficiência visual - Serviços para; Projeto de acessibilidade; Pessoas com deficiência visual; Comunicações digitais; Electronic journalism; Visually Impaired People - Services for; CNPQ::CIENCIAS SOCIAIS APLICADAS